AN ANALYSIS OF IRMAN GUSMAN'S THOUGHTS ON THE DECENTRALIZATION OF EDUCATIONAL REGULATION: REALIZING REGIONAL INDEPENDENCE IN THE NATIONAL EDUCATION SYSTEM - Rizky Firnanda; Arif Wasiatul Wafa; Retni Nur Fauziah; Ninda Faradhila (As-Sulthan Journal of Education, 2026)
Decentralization of education regulations is a strategic policy within Indonesia's national education system, aiming to grant greater authority to regions to manage education according to local needs and characteristics. Irman Gusman's thinking emphasizes the importance of regional independence as a prerequisite for achieving equity and improving the quality of national education. However, in practice, educational decentralization still faces various problems, such as imbalances in regional capacity, overlapping regulations, and weak coordination between the central and regional governments. This study aims to examine Irman Gusman's thinking on decentralization of education regulations and their relevance in realizing regional independence within the national education system. The research method used is a qualitative approach with data collection techniques through interviews, literature studies, and analysis of education policy documents. The results show that Irman Gusman's thinking emphasizes decentralization as an effort to strengthen the role of regions in formulating education policies, increasing community participation, and optimizing local potential. He believes that decentralization of education regulations must be accompanied by strengthening regional institutional capacity and proportional oversight from the central government. The conclusion of this study states that Irman Gusman's thinking is relevant in the context of national education development, particularly in promoting regional independence, provided it is supported by clear regulations, adequate human resources, and synergy between stakeholders.